2012
DOI: 10.1364/ol.37.004919
|View full text |Cite
|
Sign up to set email alerts
|

Fano resonances in disk–ring plasmonic nanostructure: strong interaction between bright dipolar and dark multipolar mode

Abstract: This Letter presents a plasmonic nanostructure consisting of a nanodisk and a nanoring. The nanodisk is outside of the nanoring. The quadrupolar, hexapolar, and octupolar resonance modes of the nanoring are excited easily by the bright dipolar mode of nanodisks. This nanostructure shows strong interaction and deep Fano dips. In addition, the resonance frequency, depth, and line width of Fano dips can be tuned by changing the geometrical parameters of the nanodisk and nanoring. These plasmonic nanostructures sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 18 publications
(23 reference statements)
1
41
0
Order By: Relevance
“…It has been demonstrated that Fano resonances can only be generated in a nonconcentric ring/disk cavity, where the structure symmetry is breaking to excite the dark quadrupolar ring mode. 7,28 The structure symmetry is not breaking for the concentric cavity dimer, but there is a Fano resonance around 852 nm ( Fig. 1(c)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that Fano resonances can only be generated in a nonconcentric ring/disk cavity, where the structure symmetry is breaking to excite the dark quadrupolar ring mode. 7,28 The structure symmetry is not breaking for the concentric cavity dimer, but there is a Fano resonance around 852 nm ( Fig. 1(c)).…”
Section: Introductionmentioning
confidence: 99%
“…18 Multiple Fano resonances have also drawn a lot of attention because they can simultaneously modify the plasmon line at several spectral positions. [19][20][21][22][23][24][25][26][27][28][29] For example, double Fano resonances are investigated in coherent plasmonic cavities. 30 Multiple Fano resonances are very suitable for multi-wavelength biosensing, and FoM can be as large as 40 by using higher order Fano resonances.…”
Section: Introductionmentioning
confidence: 99%
“…The physical principle of Fano resonance derives from the interference between beam waves which is usually correlative of the destructive interference between bright and dark modes [14][15][16]. Generally speaking, the bright mode is a super radiant which is the continuous state and directly excited by incident illumination, whereas the plasmon dark mode is a subradiant mode which is the discrete state almost has no coupling with incident illumination.…”
Section: Introductionmentioning
confidence: 99%
“…The plasmonic Fano-like resonances exhibit sharp resonance and strong light confinement and are analogues of electromagnetically induced transparency (EIT) [1]. They have been observed in various symmetric and asymmetric metallic nanostructures that include nanoshells [2][3][4][5][6], multilayered nanocones [7], rings [8][9][10][11][12], dimers [13][14][15][16][17][18][19][20], trimers [21,22], quadrumer [23,24], pentamers [25,26], hexamer [27], and nanoparticle chains [28,29]. Among all the nanostructures, the plasmonic layered nanostructures have attracted many researchers attention because these structures exhibiting multiple Fano resonances over the entire visible spectrum as well as near to mid infrared region.…”
Section: Introductionmentioning
confidence: 99%